Pengaruh Green Marketing dalam Membentuk Preferensi Konsumen Milenial terhadap Produk Ramah Lingkungan - Maulany, Soesanty (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the impact of green marketing on millennial consumer preferences in Indonesia. Using a quantitative approach with a survey of 250 respondents, this study examines the influence of four dimensions of green marketing—green product, green price, green promotion, and green place—on millennial consumer preferences. The results of the regression test showed that green product (β = 0.45, p < 0.05) and green promotion (β = 0.32, p < 0.05) had a significant positive influence on consumer preferences. In contrast, green price (β = 0.12, p > 0.05) and green place (β = 0.08, p > 0.05) showed a smaller and less significant influence. The t-test also confirmed that green products and green promotion significantly influenced millennials' purchasing decisions, while price and distribution factors had a more limited influence. The study suggests that companies should focus on eco-friendly product quality and transparent promotions to attract the attention of millennial consumers. These findings are important for companies looking to optimize their green marketing strategies to increase consumer preferences that are more concerned about sustainability.